2011
DOI: 10.1563/aaid-joi-d-09-00091.1
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Anorganic Bone Graft Associated with Platelet-Rich Plasma: Histologic Analysis in Rabbit Calvaria

Abstract: Autogenous bone tissue has regeneration potential; however, this capacity may not be sufficient in larger bone defects. The aim of this study is to histologically evaluate anorganic bovine bone grafts (GenOx Inorg) with or without platelet-rich plasma (PRP). Two bone lesions were created in calvaria of 12 rabbits. The 24 surgical lesions were separated into 3 groups: coagulous, anorganic, and anorganic with PRP. At the 4-week time point, the animals were euthanized and the grafted area removed, fixed in formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
2
3
0
8
Order By: Relevance
“…A direct comparison between the results of the present study and published reports on platelet-derived bioactive components is difficult because of the differences in the platelet preparation (PRP, PRF, and APL) and/or in the study design [26]. Nevertheless, the findings of the present study corroborate those of other animal studies, which also showed that PRP in conjunction with DBBM in critical-size rabbit calvaria [21] and frontal defect of goat [17, 20] does not improve DBBM osteoconductivity. As regards BCP, PRP in combination with BCP (ratio 60/40) was tested only in rat calvaria defects [19, 23] and no positive effect of PRP was established.…”
Section: Discussionsupporting
confidence: 76%
“…A direct comparison between the results of the present study and published reports on platelet-derived bioactive components is difficult because of the differences in the platelet preparation (PRP, PRF, and APL) and/or in the study design [26]. Nevertheless, the findings of the present study corroborate those of other animal studies, which also showed that PRP in conjunction with DBBM in critical-size rabbit calvaria [21] and frontal defect of goat [17, 20] does not improve DBBM osteoconductivity. As regards BCP, PRP in combination with BCP (ratio 60/40) was tested only in rat calvaria defects [19, 23] and no positive effect of PRP was established.…”
Section: Discussionsupporting
confidence: 76%
“…While some studies in cranial and mandibular defects showed that the addition of PRP to xenografts, alloplastic materials or scaffolds improved bone formation compared to the use of the grafts/scaffolds alone (Aghaloo, Moy & Freymiller, ; Chen, Lu, Liu, Tang & Zhang, ; El Backly, Zaky, Canciani, Saad & Eweida, ; Hirota, Matsui, Mizuki, Kishi & Watanuki, ; Kim, Kim, Kim, Lim & Kim, ; Li, Chen, Wei, Hao & Wang, ; Penteado, Colombo, Penteado, Assis & Gurgel, ; Schlegel et al., ), other studies did not confirm these findings (DeNicolo, Guyton, Cuenin, Hokett & Sharawy, ; Faratzis, Leventis, Chrysomali, Khaldi & Eleftheriadis, ; Plachokova, Dolder, Stoelinga & Jansen, ; Rocha, Ramos, Batista, Zanetta‐Barbosa & Ferro, ; Wiltfang et al., ) or showed that the use of MSCs in conjunction with bone substitutes could enhance bone regeneration more than PRP (Khojasteh, Eslaminejad & Nazarian, ). It was also shown that adding PRP to GBR (Kazakos, Lyras, Thomaidis, Agrogiannis & Botaitis, ) or to BMP (Ferraz, Schellini, Schellini, Pellizon & Hirai, ) did not accelerate the bone formation process.…”
Section: Resultsmentioning
confidence: 99%
“…O material orgânico, por ser proveniente de outra espécie, ter antigenicidade mais pronunciada do que o enxerto alógeno, e risco de transmissão de doenças como a encefalopatia espongiforme bovina ou doença da vaca louca, requer um tratamento mais rigoroso (Issa et al, 2015). Atualmente o seu uso é limitado pela quase inexistente capacidade osteoindutora e a sua relativamente rápida reabsorção (Rocha et al, 2011). Em contrapartida, o material inorgânico é um dos mais utilizados e estudados na atualidade.…”
Section: Sanzunclassified
“…Dentre esses materiais, o mais amplamente utilizado na atualidade é o osso xenógeno de origem bovina, designado de matriz óssea inorgânica ou osso inorgânico (Accorsi-Mendonça et al, 2011;Rocha et al, 2011;Manfro et al, 2014;Rocha et al, 2014;Issa et al, 2015). A produção do osso inorgânico bovino ocorre por meio de um processo de desproteinização de osso esponjoso bovino a altas temperaturas e de procedimentos químicos de limpeza resultando na completa eliminação das proteínas do osso e na produção de uma matriz óssea mineral predominantemente de hidroxiapatita natural, porosa e não antigênica (Accorsi-Mendonça et al, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation